Reducing the Genetic Redundancy of Arabidopsis PHOSPHATE TRANSPORTER1 Transporters to Study Phosphate Uptake and Signaling. Issue 4 (10th February 2015) - Ayadi, Amal; David, Pascale; Arrighi, Jean-François; Chiarenza, Serge; Thibaud, Marie-Christine; Nussaume, Laurent; Marin, Elena
Abstract : Disruption of four genes severely reduces the active phosphate transport but does not impact phosphate sensing capacities in Arabidopsis. Abstract: Arabidopsis ( Arabidopsis thaliana ) absorbs inorganic phosphate (Pi ) from the soil through an active transport process mediated by the nine members of the PHOSPHATE TRANSPORTER1 (PHT1) family. These proteins share a high level of similarity (greater than 61%), with overlapping expression patterns. The resulting genetic and functional redundancy prevents the analysis of their specific roles. To overcome this difficulty, our approach combined several mutations with gene silencing to inactivate multiple members of the PHT1 family, including a cluster of genes localized on chromosome 5 ( PHT1;1, PHT1;2, and PHT1;3 ). Physiological analyses of these lines established that these three genes, along with PHT1;4, are the main contributors to Pi uptake. Furthermore, PHT1;1 plays an important role in translocation from roots to leaves in high phosphate conditions. These genetic tools also revealed that some PHT1 transporters likely exhibit a dual affinity for phosphate, suggesting that their activity is posttranslationally controlled. These lines display significant phosphate deficiency-related phenotypes (e.g. biomass and yield) due to a massive (80%–96%) reduction in phosphate uptake activities. These defects limited the amount of internal Pi pool, inducing compensatory mechanisms triggered by the systemic Pi starvation response. Such reactions have been uncoupled from PHT1 activity, suggesting that systemic Pi sensing is most probably acting downstream of PHT1.